The Role of TikTok Algorithm in Directing Religious Content Based on User Perception and Prophetic Character - Mubarok, Darojah Alawiyah; Muttaqin, Isti Maghfira; Sundari, Sri Sukma; Ramadhan, Dinda Nur; Hidayat, Arif (Institut Agama Islam Negeri Kediri, 2025)
TikTok has now become one of the most influential social media platforms in the dissemination of religious content. Supported by artificial intelligence, TikTok's algorithm can automatically adjust and recommend religious content to users based on their preferences and interaction patterns. This study aims to analyze the role of TikTok's algorithm in influencing the consumption of religious content from the users' perspective while examining it through the lens of prophetic character. The research employs a qualitative approach and secondary data analysis from academic literature. The findings indicate that TikTok's algorithm plays a dual role: as a facilitator in the dissemination of religious messages and as a factor that may introduce algorithmic bias in religious content exposure. From the perspective of prophetic character, it is crucial to assess how this algorithm contributes to the spread of authentic and moderate Islamic values while reducing potential distortions in religious understanding. Therefore, more ethical strategies are needed in utilizing TikTok's algorithm to ensure alignment with religious principles and sustainable spiritual education.